2012
DOI: 10.1242/dev.068817
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila G-protein-coupled receptor kinase 2 regulates cAMP-dependent Hedgehog signaling

Abstract: G-protein-coupled receptor kinases (GRKs) play a conserved role in Hedgehog (Hh) signaling. In several systems, GRKs are required for efficient Hh target gene expression. Their principal target appears to be Smoothened (Smo), the intracellular signal-generating component of the pathway and a member of the G-protein-coupled receptor (GPCR) protein family. In Drosophila, a GRK called Gprk2 is needed for internalization and downregulation of activated Smo, consistent with the typical role of these kinases in nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 55 publications
3
27
0
Order By: Relevance
“…We previously reported that Gprk2 affects phosphorylation of Smo at sites other than GPS1 and GPS2 [19]. Even when using a PKA- and CKI-phosphomimetic form of Smo, Smo SD [5] to circumvent the effects of gprk2 depletion on cAMP levels, there was a substantial reduction of Smo phosphorylation (detected by increased mobility in SDS-PAGE) upon dsRNA-mediated depletion of Gprk2 that could not be accounted for by the GPS sites (Figure S1A).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…We previously reported that Gprk2 affects phosphorylation of Smo at sites other than GPS1 and GPS2 [19]. Even when using a PKA- and CKI-phosphomimetic form of Smo, Smo SD [5] to circumvent the effects of gprk2 depletion on cAMP levels, there was a substantial reduction of Smo phosphorylation (detected by increased mobility in SDS-PAGE) upon dsRNA-mediated depletion of Gprk2 that could not be accounted for by the GPS sites (Figure S1A).…”
Section: Resultsmentioning
confidence: 93%
“…On the other hand, loss of gprk2 causes a reduction in cyclic AMP (cAMP) levels, affecting PKA-dependent Smo activation. Target gene expression can be largely rescued in gprk2 mutants by increasing cAMP levels, suggesting that this indirect effect of Gprk2 on Smo plays an important role in Hh pathway function [19].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that Shh signals through the noncanonical pathway in primary LF, which, as others have shown, is sufficient to increase fibroblast migration (35). Smoothened is regulated by other mechanisms: 1) it is dependent on intraflagellar transport proteins for entry and translocation within the primary cilium; 2) it is phosphorylated and activated by PKA, which is dependent on adequate intracellular cAMP; 3) smoothened is ubiquitinated and degraded, a process that is regulated by a ubiquitin-specific protease USP8; and 4) smoothened activity is also influenced by phosphorylation of suppressor of fused (SuFu) by PKA or glycogen synthase kinase-3␤ (7,19,48). In primary LF, negative regulation through one or more of these pathways could dampen signaling through the canonical pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that Gprk2 acts in Hedgehog (Hh) signaling for imaginal disc patterning (Molnar et al, 2007;Chen et al, 2010;Cheng et al, 2012). In this process, Gprk2 phosphorylates a GPCR, Smoothened, and potentiates Hh signaling.…”
Section: Research Article Gprk2 In Drosophila Gastrulationmentioning
confidence: 99%
“…For instance, mouse Grk1 knockout retinal cells produce stronger and longer outputs upon receiving a flash of light (Chen et al, 1999), suggesting that GRK1 regulates the sensitivity and duration of signaling. Recently, it has been shown that a Drosophila GPCR kinase, Gprk2, plays diverse roles in various biological processes, such as egg morphogenesis, olfactory response and tissue patterning (Schneider and Spradling, 1997;Molnar et al, 2007;Tanoue et al, 2008;Chen et al, 2010;Cheng et al, 2012). However, the role of Gprk2 in embryonic development has remained unclear.…”
Section: Introductionmentioning
confidence: 99%